2000
DOI: 10.1063/1.874027
|View full text |Cite
|
Sign up to set email alerts
|

Energetic proton production from relativistic laser interaction with high density plasmas

Abstract: Energetic protons up to 30 MeV have been measured from high intensity laser interactions (⩽5×1019 W/cm2) with solid density plasmas. Up to 1012 protons (> 2 MeV) were observed at the rear of thin aluminum foil targets and measurements of their angular deflection were made. Similar energies were measured from ions produced from the front of the foils. Nuclear activation and track detector measurements suggest that the protons measured at the rear originate from the front surface of the target and are ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
62
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 36 publications
6
62
1
Order By: Relevance
“…We found that the theoretical dependences of the ion-generation efficiency versus laser intensity and plasma profiles agree well with recent experiments at the Center of Ultrafast Optical Science at laser intensities of I ≤ 6 × 10 18 W/cm 2 [5] and the data on maximum ion energies from the experiments performed at the Rutherford Appleton Laboratory on the Vulcan laser [13].…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…We found that the theoretical dependences of the ion-generation efficiency versus laser intensity and plasma profiles agree well with recent experiments at the Center of Ultrafast Optical Science at laser intensities of I ≤ 6 × 10 18 W/cm 2 [5] and the data on maximum ion energies from the experiments performed at the Rutherford Appleton Laboratory on the Vulcan laser [13].…”
Section: Introductionsupporting
confidence: 74%
“…The results obtained from some experiments [5,13] provide evidence that the observed MeV-ions were generated and accelerated in the plasma at the front of the target, conflicting with experiments [3,23] that indicated that proton acceleration took place at the back of the target. The electrostatic model of ion acceleration suggests that the origin of the ions is the same for both of these experiments and that the only difference is in the plasma thickness: whether or not the plasma extends to the rear surface.…”
Section: Introductioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Laser-driven ion sources [1,2,3,4,5,6,7] are considered to be the hot candidates for various important applications in nuclear physics, medicine, biology, material sciences, plasma field tomography [8,9,10]. When multiterawatt laser pulses are shot on solid state targets, copious amounts of multi-MeV ions -both protons and highly charged heavier ions -are generated [11].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments at this intensity level are of great interest because of a number of applications such as fast ignition [1], particle acceleration [2][3][4], hard x-ray [2][3][4] and high order harmonic generation [5], etc. Plasma instabilities can play an important role in these interactions.…”
Section: Introductionmentioning
confidence: 99%